KONTRIBUSI KOORDINASI MATA-TANGAN DAN KEKUATAN OTOT LENGAN PADA KETEPATAN SMASH BULUTANGKIS CLUB PB. BANKRIAU KEPRI PEKANBARU - Septiyani, Indri; Apriani, Leni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to identify the contribution of eye-hand coordination and arm muscle strength to smash accuracy in badminton club Pb.BankRiau Kepri Pekanbaru. The research was conducted by collecting data from 10 badminton players who are active in the club. The data collected includes the results of eye-hand coordination tests, hand muscle strength tests, and smash accuracy. The sampling technique was carried out using total sampling technique. Data analysis techniques are carried out using product moment and double correlation. Based on the results of the study, the conclusions obtained in the study are: There is a contribution but not significant hand-eye coordination to the accuracy of badminton smash athletes Pb.BankRiau Kepri Pekanbaru with a percentage of 5.2%. The calculation results obtained a rcount value of -0.228 < rtable = 0.628) there is a contribution but not significant arm muscle strength to the accuracy of badminton smash club athletes Pb.BankRiau Kepri Pekanbaru with a percentage of 3.5%. The calculation results obtained a rcount value of 0.118 < rtable = 0.632) there is a contribution but not significant eye-hand coordination and arm muscle strength on the accuracy of badminton smash club Pb.BankRiau Kepri Pekanbaru with a percentage of 7.2%. The calculation results obtained the value of rcount -0.268 < rtabel = 0.632).